2015
DOI: 10.1097/jcp.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Psychotropic Medication Use Reported by Borderline Patients and Axis II Comparison Subjects Over 16 Years of Prospective Follow-Up

Abstract: The purpose of this study was to assess the classes and types of psychotropic medication reported by borderline patients and axis II comparison subjects over 16 years of prospective follow-up. Medication use was assessed at baseline using a semistructured interview of proven reliability and validity as well as its follow-up analog at eight contiguous two-year follow-up periods. A significantly higher percentage of borderline patients than axis II comparison subjects reported taking an antidepressant, an anxiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 17 publications
(25 reference statements)
3
27
0
1
Order By: Relevance
“…It may be that these dysphoric affects are in this stubborn group of symptoms because they represent inadequately treated mood and/or anxiety disorders, which are common co-occurring disorders among borderline patients (18). However, a high proportion of borderline patients used psychosocial treatments (19) and psychotropic medications (20) over time. It may also be that these symptoms represent a reasonable response to the limited lives led by a substantial percentage of borderline patients—lives marked by social isolation and serious vocational impairment (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that these dysphoric affects are in this stubborn group of symptoms because they represent inadequately treated mood and/or anxiety disorders, which are common co-occurring disorders among borderline patients (18). However, a high proportion of borderline patients used psychosocial treatments (19) and psychotropic medications (20) over time. It may also be that these symptoms represent a reasonable response to the limited lives led by a substantial percentage of borderline patients—lives marked by social isolation and serious vocational impairment (21).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that about 90% of those in both patient groups were in individual therapy and taking psychotropic medications at baseline and about 70% were participating in each of these outpatient modalities during each follow-up period (19). More specifically, 65% of borderline patients were in individual therapy and 71% were taking standing medications at 16-year follow-up, with 58% taking antidepressants, 26% taking anxiolytics, 28% taking antipsychotics, and 29% taking mood stabilizers (20). Thus, it is difficult to know if these results would generalize to a less disturbed group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zanarini and colleagues (Zanarini, Frankenburg, Reich, Harned, & Fitzmaurice, 2015) investigated psychiatric medication use in BPD compared to other personality disorders. They found that people with BPD took more antidepressants (1.3 times more), antipsychotics (2.6 times more) and mood stabilizers (3 times more) than did comparison subjects.…”
Section: Psychiatric Medication Usementioning
confidence: 99%
“…In addition, it has been observed that low doses of secondgeneration antipsychotics could improve cognitive-perceptual symptoms [4]. Antidepressants, anxiolytics, antipsychotics, and mood stabilizers are used by a significantly higher percentage of borderline patients than other people with personality disorders [5]. This is not surprising as it is recognized that borderline psychopathology is more severe than that of other types of personality disorders.…”
Section: Cluster B Personality Disorders (Antisocial Borderline Hismentioning
confidence: 99%